1994
DOI: 10.1161/01.str.25.9.1788
|View full text |Cite
|
Sign up to set email alerts
|

Callosal atrophy in patients with lacunar infarction and extensive leukoaraiosis. An indicator of cognitive impairment.

Abstract: It is unclear why only some patients with lacunar infarction and radiological evidence of diffuse white matter abnormalities have dementia. The purpose of this study is to investigate the value of callosal atrophy as an indicator of cognitive impairment. We used magnetic resonance imaging to evaluate 11 right-handed male patients with lacunar infarction and extensive white matter hypodensities on computed tomography (8 with dementia and 3 without dementia). The midsagittal corpus callosum area on T1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Nevertheless, our results are in accordance with the studies of Yamauchi et al (1994 and1995). 20,33 They reported that callosal atrophy occurs in patients with cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, our results are in accordance with the studies of Yamauchi et al (1994 and1995). 20,33 They reported that callosal atrophy occurs in patients with cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 93%
“…20,33 They reported that callosal atrophy occurs in patients with cerebrovascular disease. In contrast, Pantel et al (1998) 34 failed to demonstrate significant differences between vascular dementia and controls with respect to global and regional callosal size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, patients with extensive WMLs show a variable severity of global cognitive impairment, with some patients showing vascular dementia, whereas others have almost normal cognitive function despite extensive WMLs. [7][8][9] A longitudinal study demonstrated that further global cognitive deterioration occurs with time in patients with extensive WMLs whose cognitive impairment was mild initially. 6 Therefore, understanding the pathophysiology that may cause a variable severity of cognitive impairment in patients with similar extensive WMLs may lead to the development of optimal therapeutic interventions preventing vascular dementia.…”
mentioning
confidence: 99%
“…8,9 The corpus callosum consists of interhemispheric corticocortical connecting fibers, and most of the fibers traverse the HDWM while approaching the contralateral hemisphere. 9 In extensive leukoaraiosis, ischemic insult to the HDWM may affect all of the component fiber tracts, irrespective of their fiber directions.…”
mentioning
confidence: 99%